Comparison of four models simulating phosphorus dynamics in Lake Vänern, Sweden - M. Dahl; B. C. Pers (Hydrology and Earth System Sciences, 2004)
This paper compares four water quality models applied to Lake Vänern, Sweden. The comparison is focused on phosphorus, the primary limiting nutrient in Lake Vänern. Two of the models, FYRISÅ and HBVNP, are simple and were developed as parts of catchment models. Two other models, called LEEDS and BIOLA, are more comprehensive lake models. The models were calibrated using data from the period 1985–1992 and validated using data from the period 1993–2000. The fit to calibration data is similar for the FYRISÅ, HBVNP, and LEEDS models, and slightly worse for the BIOLA model. All models fit the validation data almost as well as the calibration data. The models’ behaviour was tested in two representative scenarios. An increase of emissions by 40% from a pulp and paper mill has a negligible effect on the water quality, while a decrease in phosphorus load by 14% (accomplished by better waste-water treatment in rural households) gives a considerable decrease in phosphorus concentration in the lake. Still, the results of the scenarios vary between the models. Keywords: lake, phosphorus, model, scenarios, simulation